FUNCTIONAL USE OF EXPRESSIVE MEANS AND STYLISTIC DEVICES - Axmedov, Namoz Boxodirovich (Educational Research in Universal Sciences, 2023)
The language strategies, through which an author develops particular stylistic aspects in order that the content he provides satisfies the appropriate purposes, are discussed in the subsequent paragraphs. Due to their ability to produce specific aesthetic effects, the language means we examine later in this section could be considered stylistic means. Our debate will be more productive if we distinguish the difference between expressive means and stylistic devices.